PENGARUH PENAMBAHAN KELOPAK ROSELLATERHADAP MUTU SENSORI PERMEN JELLY DARI ALBEDO SEMANGKA - Meieri Adelila Saragih; Vonny Setiaries Johan; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Jelly candy is one of the popular candy among people especially children. The purpose of this research was to obtain the best ratio albedo of watermelon and rosella flower petals in the manufacture of jelly candy. This research used Complete Randomized Design (CRD) Experiment with five treatments and three replications. If F count equal or bigger than F table, then will do next test DNMRT (Duncan’s New Multiple Range Test) at level 5%. The treatments in this research were A1R1 (ratio of watermelon albedo extracts and rosella petals extracts 90 : 10), A2R2 (ratio of watermelon albedo extracts and rosella petals extracts 80 : 20), A3R3 (ratio of watermelon albedo extracts and rosella petals extracts 70 : 30), A4R4 (ratio of watermelon albedo extracts and rosella petals extracts 60 : 40) and A5R5 (ratio of watermelon albedo extracts and rosella petals extracts 50 : 50). The results showed that extract albedo of watermelon and rosella petals significantly affected the description of sensory test to colour, texture, flavor, teste and hedonic test. The best formulation of jelly candy was A5R5 with organoleptic scores of A5R5 were colour 4.46 (red), taste 3.83 (acid), texture 2.91 (rather chewy), flavour 3.83 (rosella flavour) and 4.36 (hedonic over all test). Keywords: Jelly candy, albedo of watermelon, petals of rosella.